The balanced scorecard : translating strategy into action - Kaplan, Robert S. (Harvard Business School Press, 1996)
Here is the book - by the recognized architects of the Balanced Scorecard - that shows how managers can use this revolutionary tool to mobilize their people to fulfill the company's mission. More than just a measurement system, the Balanced Scorecard is a management system that can channel the energies, abilities, and specific knowledge held by people throughout the organization toward achieving long-term strategic goals.